Membrane transport mechanisms of choline in human intestinal epithelial LS180 cells. (29th October 2014) - Horie, Asuka; Ishida, Kazuya; Watanabe, Yuri; Shibata, Kaito; Hashimoto, Yukiya
ABSTRACT The aim of the present study was to investigate the membrane transport mechanisms of choline using human intestinal epithelial LS180 cells. The mRNA of choline transporter‐like proteins (CTLs) was expressed significantly in LS180 cells, and the rank order was CTL1 > CTL4 > CTL3 > CTL2 > CTL5. In contrast, the mRNA expression of other choline transporters, organic cation transporter (OCT) 1, OCT2 and high‐affinity choline transporter 1 (CHT1), was considerably lower in LS180 cells. Five mm unlabelled choline, hemicolinium‐3 and guanidine, but not tetraethylammonium, inhibited the cellular uptake of 100 µm choline in LS180 cells. The uptake of choline into LS180 cells was virtually Na+‐independent. The uptake of choline was significantly decreased by acidification of the extracellular pH; however, it was not increased by alkalization of the extracellular pH. In addition, both acidification and alkalization of intracellular pH decreased the uptake of choline, indicating that the choline uptake in LS180 cells is not stimulated by the outward H+ gradient. On the other hand, the uptake of choline was decreased by membrane depolarization along with increasing extracellular K+ concentration. In addition, the Na+‐independent uptake of choline was saturable, and the Km value was estimated to be 108 µm. These findings suggest that the uptake of choline into LS180 cells is membrane potential‐dependent, but not outward H+ gradient‐dependent. Copyright © 2014 John Wiley & Sons, Ltd.